COMPUTER PHOBIA AMONG SUPERVISOR, PHYSICAL EDUCATION: MYTH V/S REALITY - Yadav, D.S; Malhotra, Deepika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Physical education is crucial for the holistic development of students, promoting physical fitness, mental well-being, and essential life skills such as teamwork, discipline, and leadership. It fosters lifelong habits of exercise and health consciousness while enhancing cognitive abilities, which contribute to better academic performance. The integration of technology in physical education has significantly improved the effectiveness of teaching, learning, and program management, making activities more engaging and accessible. However, the digital shift has highlighted challenges, particularly among Physical Education Supervisors who may experience computer phobia. This study examines the prevalence of computer phobia among Physical Education Supervisors in Delhi, focusing on gender differences. Using a descriptive research method and survey data from 17 supervisors (5 male, 12 female), the study finds that computer phobia is moderately prevalent among these professionals, with male supervisors exhibiting significantly higher levels of fear compared to their female counterparts.